Investigation of the dynamics of the Z-pinch imploding plasma for a laser-assisted discharge-produced Sn plasma EUV source - Zhu, Q; Yamada, J; Kishi, N; Watanabe, M; Okino, A; Horioka, K; Hotta, E (Journal of Physics D: Applied Physics, 2011)
Dynamics of the imploding plasma and its relations to the 13.5 nm EUV emissions have been experimentally investigated for a laser-assisted Sn based discharge-produced plasma EUV source. The behaviours and two-dimensional electron density distributions of the EUV-emitting plasma were obtained using the time-resolved shadowgraph and Nomarski interferometric techniques. Observation of the plasma piston in the prepinch phase justified the validity of the zero-dimensional thin-shell model, from which the ion charge state of the prepinch plasma in the cathode region was estimated. The sausage ( m = 0) instability that usually enhances the EUV emission was observed, with the radial electron density distribution that displays a concave shape at the crest of the plasma and a bell shape at the neck; the maximum of the electron density is located at one peak of the concave distribution at the crest instead of the neck. Intense EUV emission was produced by the Z -pinch plasma with the electron density (2.0–3.0) × 10 18 cm −3 . Moreover, the shock waves generated in the anode region can also produce in-band EUV emission with the intensity of 30% of that from the Z-pinch plasma.